2022
DOI: 10.51458/bstd.2022.23
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Mineral and Heavy Metal Contents of Propolis Additive Ice Cream

Abstract: In this study, it was aimed to add a functional food property to the ice cream, which is a popular food, by adding propolis. At the same time, study aims to provide a widespread consumption potential to propolis which is impossible to be consumed in raw form and whose benefits and functional properties not known by consumers. 6 groups of ice cream containing control group and 0.1%, 0.2%, 0.3%, 0.4%, and 0.5% propolis powder were obtained from prepared ice cream mix. Mineral substance analysis to propolis sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Adding different ratios of raw propolis powder into ayran (0%–0.75%, w/v) and buttermilk (1%–3%, w/v), Çelik (2016) reported that increasing the ratio of propolis powder in both products resulted in an increase in their DPPH radical scavenging activities and phenolic contents, which decreased during storage. Mehmetoğlu (2019) reported that the addition of propolis (0.1%–0.5%) into ice creams significantly increased their antioxidant activities. Aktaş (2019) used microencapsulated PE in the production of banana‐flavored pudding and stated that the antioxidant activities and phenolic contents of pudding samples significantly increased with an increase in the ratio of propolis while there was a decrease in these values during storage.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Adding different ratios of raw propolis powder into ayran (0%–0.75%, w/v) and buttermilk (1%–3%, w/v), Çelik (2016) reported that increasing the ratio of propolis powder in both products resulted in an increase in their DPPH radical scavenging activities and phenolic contents, which decreased during storage. Mehmetoğlu (2019) reported that the addition of propolis (0.1%–0.5%) into ice creams significantly increased their antioxidant activities. Aktaş (2019) used microencapsulated PE in the production of banana‐flavored pudding and stated that the antioxidant activities and phenolic contents of pudding samples significantly increased with an increase in the ratio of propolis while there was a decrease in these values during storage.…”
Section: Resultsmentioning
confidence: 99%
“…Determining the sensory properties of yogurts with propolis and honey at different ratios during storage, Çifci ( 2015 ) reported that the odor and texture scores of samples decreased as propolis ratio and storage time increased. Mehmetoğlu ( 2019 ) used propolis powder (0.1%–0.5%) in ice cream production and reported its adverse effect on the sensory properties of ice cream samples while the most liked one was the control sample. Adding microencapsulated PE into cake samples at different ratios (2.5%, 5.0%, 7.5%, and 10.0%, w/w), Acun ( 2021 ) found that cakes with more than 5.0% PE were not preferred by panelists.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations